Meningkatkan Potensi Ekonomi Kreatif Melalui UMKM Di Desa Bayung Gede - Putu Pande R. Aprilyani Dewi; Ni Putu Budiadnyani; I Gusti Agung Ayu Pramita Indraswari (JURNAL PENGABDIAN MASYARAKAT AKADEMISI, 2023)
The most frequently encountered non-organic waste issue is plastic bag waste which is widespread in society, even though plastic packaging is a material that is difficult to decompose or destroy. One simple activity that can be done to reduce plastic waste is to use paper bags. The process of making paper bags can use materials that are around us, such as waste paper. The activity carried out in community service is a socialization carried out in increasing the creative economic potential for the community in Bayung Gede Village, Kintamani District, Bangli Regency, Bali Province, in October 2022. From the community service activities that have been carried out in Bayung Gede Village, it can be concluded that participants who take part in the training can increase the selling value of products by using the skills they have and can increase the economic value in Bayung Gede Village.